SYMPTOMATIC EARLY-ONSET X-LINKED RETINOSCHISIS: Clinical Presentation and Outcomes. Issue 2 (February 2023) - Piquin, Gwendoline; Abdelmassih, Youssef; Martin, Gilles; Edelson, Catherine; Metge, Florence; Caputo, Georges; Chapron, Thibaut
Abstract : X-linked retinoschisis is a common pediatric retinal dystrophy that is usually diagnosed at school age but can be also present much earlier. We describe clinical characteristics and outcomes of patients with symptomatic X-linked retinoschisis diagnosed younger than 2 years. Abstract : Purpose: To describe clinical characteristics and outcomes of children with early-onset X-linked retinoschisis. Methods: In this retrospective consecutive case series, we included children diagnosed with symptomatic X-linked retinoschisis younger than 2 years. Presenting signs, clinical characteristics, treatments, and outcomes were recorded. Results: Seven patients (14 eyes) with a mean age of 17.14 ± 6.28 months were included. Strabismus was the most common presenting symptom (6 of 7 patients, 86%). Clinical signs at the first diagnosis included peripheral retinoschisis in 13 eyes (13/14, 93%), of which 5 (5/13, 38%) were bullous, vitreous hemorrhage in 3 eyes (3/14, 21%), and retinal detachment in 3 eyes (3/14, 21%). The macula was involved in all eyes: It was detached in 2 eyes (2/14, 14%) and involved in the peripheral schisis in 4 eyes (4/14, 29%). In all remaining eyes, optical coherence tomography revealed foveoschisis. Six eyes (6/14, 42%) received surgery. At the last follow-up, visual acuity, when available, ranged from no light perception to 20/40, and no children had persistent retinal detachment. Conclusion: Children with early-onset X-linked retinoschisis had severe forms. All children had peripheral retinoschisis which was often bullous and extended to the macula. Diagnosis is often clinical but handheld optical coherence tomography can be helpful in atypical forms. Complications requiring surgical management are frequent.